PARITAS DAN USIA IBU DENGAN ANEMIA KEHAMILAN DI PUSKESMAS NELAYAN KABUPATEN GRESIK - Dwi Fitriyatul Arifah; Siti Mudlikah (Jurnal Kebidanan, 2024)
The physiological alterations in blood circulation that occur during pregnancy result in an increase in blood volume, a condition known as hypervolemia. This increase also affects the volume of plasma and erythrocytes (red blood cells), leading to an imbalance characterized by a decrease in Hemoglobin concentration in the blood. This imbalance poses a risk of iron deficiency anemia in pregnant women. The objective of this study is to investigate the correlation between parity and maternal age with the incidence of anemia during pregnancy. Methodology: Analytical observational design, cross-sectional approach. Population of 48 first trimester pregnant women. Purposive sampling, sample of 40 pregnant women, age and parity data obtained from questionnaires and hemoglobin level data from measuring Hb levels of pregnant women using the Easy-Touch Hb tool.The statistical analysis was conducted using the Rank Spearman test. Results: The multiparous pregnant women 17 people (42.5%), aged 20-35 years 32 people (80.0%), Pregnant women who were not anemic 22 people (55.%), mild anemia 8 people (20%), anemia moderate10 (25%), Statistical analysis showed that there was no relationship between parity and pregnancy anemia (? 0.199) and there was no relationship between maternal age and pregnancy anemia at the Gresik Regency Nelayan Community Health Center (? 0.852). Conclusion: There is no relationship between parity and maternal age with pregnancy anemia. Factors that cause anemia vary between pregnant women and other pregnant women, so it is hoped that treatment of pregnancy anemia is based on the cause.